Synthesis and Degradation of Cadmium-Free InP and InPZn/ZnS Quantum Dots in Solution - Brown, Richard P (Langmuir : the ACS journal of surfaces and colloids, 2018)
This study advances the chemical research community toward the goal of replacing toxic cadmium-containing quantum dots (QDs) with environmentally benign InP QDs. The InP QD synthesis uniquely combines the previously reported use of InP magic-sized clusters (MSCs) as a single-source precursor for indium and phosphorus to form InP QDs, with zinc incorporation and subsequent ZnS shelling, to form InPZn/ZnS QDs with luminescence properties comparable to those of commonly used cadmium-containing luminescent QDs. The resulting InPZn/ZnS QDs have an emission quantum yield of about 50% across a broad range of emission peak wavelengths and emission peaks averaging 50 nm fwhm. The emission peak wavelength can be easily tuned by varying the Zn/In ratio in the reaction mixture. The strategy of using zinc stearate to tune the emission properties is advantageous as it does not lead to a loss of emission quantum yield or emission peak broadening. Although the initial optical properties of InP and InPZn/ZnS QDs are promising, thermal stability measurements of InPZn QDs show significant degradation in the absence of a shell compared to the CdSe QDs particularly at increased temperature in the presence of oxygen, which is indicative of thermal oxidation. There is no significant difference in the degradation rate of InP QDs made from molecular precursors and from MSCs. Additionally, the emission intensity and quantum yield of InPZn/ZnS QDs when purified and diluted in organic solvents under ambient conditions decrease significantly compared to those of CdSe/ZnS QDs. This indicates instability of the ZnS shell when prepared by common literature methods. This must be improved to realize high-quality, robust Cd-free QDs with the capability of replacing CdSe QDs in QD technologies